Diffusion‐weighted MRI of breast lesions: a prospective clinical investigation of the quantitative imaging biomarker characteristics of reproducibility, repeatability, and diagnostic accuracy. (24th August 2016) - Spick, Claudio; Bickel, Hubert; Pinker, Katja; Bernathova, Maria; Kapetas, Panagiotis; Woitek, Ramona; Clauser, Paola; Polanec, Stephan H.; Rudas, Margaretha; Bartsch, Rupert; Helbich, Thomas H.; Baltzer, Pascal A.
Abstract : Diffusion‐weighted MRI (DWI) provides insights into tissue microstructure by visualization and quantification of water diffusivity. Quantitative evaluation of the apparent diffusion coefficient (ADC) obtained from DWI has been proven helpful for differentiating between malignant and benign breast lesions, for cancer subtyping in breast cancer patients, and for prediction of response to neoadjuvant chemotherapy. However, to further establish DWI of breast lesions it is important to evaluate the quantitative imaging biomarker (QIB) characteristics of reproducibility, repeatability, and diagnostic accuracy. In this intra‐individual prospective clinical study 40 consecutive patients with suspicious findings, scheduled for biopsy, underwent an identical 3T breast MRI protocol of the breast on two consecutive days (>24 h). Mean ADC of target lesions was assessed (two independent readers) in four separate sessions. Reproducibility, repeatability, and diagnostic accuracy between examinations (E1, E2), readers (R1, R2), and measurements (M1, M2) were assessed with intraclass correlation coefficients (ICCs), coefficients of variation (CVs), Bland–Altman plots, and receiver operating characteristic (ROC) analysis with calculation of the area under the ROC curve (AUC). The standard of reference was either histopathology ( n = 38) or imaging follow‐up of up to 24 months ( n = 2). Eighty breast MRI examinations (median E1–E2, 2 ± 1.7 days, 95% confidence interval (CI) 1–2 days, range 1–11 days) in 40 patients (mean age 56, standard deviation (SD) ±14) were evaluated. In 55 target lesions (mean size 25.2 ± 20.8 (SD) mm, range 6–106 mm), mean ADC values were significantly ( P < 0.0001) higher in benign (1.38, 95% CI 1.27–1.49 × 10 −3 mm 2 /s) compared with malignant (0.86, 95% CI 0.81–0.91 × 10 − 3 mm 2 /s) lesions. Reproducibility and repeatability showed high agreement for repeated examinations, readers, and measurements (all ICCs >0.9, CVs 3.2–8%), indicating little variation. Bland–Altman plots demonstrated no systematic differences, and diagnostic accuracy was not significantly different in the two repeated examinations (all ROC curves >0.91, P > 0.05). High reproducibility, repeatability, and diagnostic accuracy of DWI provide reliable characteristics for its use as a potential QIB, to further improve breast lesion detection, characterization, and treatment monitoring of breast lesions. Abstract : In an intra‐individual clinical study the quantitative imaging biomarker characteristics for DWI of breast lesions were evaluated. Both reproducibility and repeatability demonstrated an almost perfect agreement (all intraclass correlation coefficient values >0.9) with little variation (all coefficients of variation 3.2–8%). Diagnostic accuracy showed no significant difference in two repeated identical examinations (all ROC curves >0.91, P > 0.05). Consequently, DWI of breast lesions provides reliable characteristics for use as a potential quantitative imaging biomarker, to further improve breast lesion detection, characterization, and treatment monitoring.